Motivasi dan Kepuasan Ibu Hamil Terhadap pelayanan Antenatal Care Di Puskesmas Atapupu , Belu, NTT - Alberth M. Bau Mali (Poltekkes Kemenkes Kupang, 2021)
Abstrak Antenatal care or what is often called a pregnancy check is a service by professional health workers to pregnant women during their pregnancy which is carried out in accordance with Antenatal service standards, namely Midwifery Service Standards (SPK) at least 4 checks during pregnancy. The increase in ANC services is influenced by the utilization of Antenatal service users. Many factors can cause the level of utilization of ANC services including patient satisfaction, inability in terms of costs, distance from service locations or health workers. In addition to the factors of pregnant women, these factors can affect the success of service coverage for pregnant women. Based on Atapupu puskesmas profile data, the coverage of K1 pregnant women visits at Atapupu health centers in 2016 was still below the target of 79.9% of the Minimum Service Standards (SPM) target of 100%, while the coverage of K4 pregnant women visits in 2016 was also below the target of 49.8%. of the SPM target of 97%.. Research Objectives: Identification of the Relationship between Motivation and Goals of Pregnant Women on Antenatal Care ServicesResearch Methods: Descriptive research with cross sectional methodResearch Results: Most pregnant women get high satisfaction and motivation to do Antenatal Care at Atapupu Public Health CenterKey Word : Motivation, Satisfaction, ANC